Mining the social web, LinkedIn : learn how to access, download, analyze, and visualize LinkedIn data - Klassen, Mikhail (O'Reilly Media, 2017)
"LinkedIn is the largest professional social network in the world and is used by millions of job seekers, employers, recruiters, and other professionals. How can we mine this data to gain deeper insights into our professional networks? Based on content from Matthew Russell's book "Mining the Social Web" (O'Reilly), this course shows you how to access and download LinkedIn data; as well as how to perform clustering analysis and geographic analysis, and how to visualize data in new and informative ways. The course works best for learners with some basic Python experience."--Resource description page.